Evolving Problems of Practice: How a Teacher's Reflective Courses of Action Contributed to Her Learning and Change. (2nd October 2021) - Popp, Jacquelynn S.
ABSTRACT: Although literature emphasizes the value of recursive reflection on problems of practice to facilitate teacher learning and change, few studies investigate teachers' iterative, evolving reflections on problems that emerge in their efforts to change their practice over time. This case study provides an in-depth, longitudinal analysis of one teacher's incremental trajectory of change through examining her reflective discourse in pre- and post-observational planning and debriefing meetings with researchers over two-and-a-half school years. The middle school teacher was intentionally focused on changing her practice to support students' historical inquiry, shifting from a more traditional, authoritative approach to a disciplinary-inquiry stance. Analysis entailed mapping the teacher's talk about problems of practice in planning/debriefing meetings and how the evolution of her framing of problems was influenced by reflective courses of action. Analysis revealed the teacher's courses of action differed depending on the type of problem she addressed and that these courses of action contributed to changes in her knowledge, practice, and dispositions. The paper addresses implications for studying and supporting teacher learning and change.